Characterization of Ripening Bananas by Monitoring the Amino Acid Composition by Gas Chromatography–Mass Spectrometry With Selected Ion Monitoring and Star Pattern Analysis. (2nd November 2019) - Lee, Hyeon-Seong; Kim, Young-Bae; Seo, Chan; Ji, Moongi; Min, Jewuk; Choi, Subin; Kim, Hyun-Bin; Park, Hyung-Jin; Lee, Gwang; Lee, Wonjae; Paik, Man-Jeong
Abstract: Bananas are a well-known healthy food that contain various functional amino acids (AAs) whose concentrations may vary during ripening. Thus, amino acid profiling analysis was performed at different stages of ripeness in bananas by gas chromatography–mass spectrometry (GC-MS) using selected ion monitoring (SIM) with ethoxycarbonyl/ tert -butyldimethylsilyl (EOC/TBDMS) derivatives. The variability of the amino acids in ripening was subsequently explored by star pattern analysis after normalization to the corresponding mean values of the unripe bananas. Significant alterations of amino acids were found in ripe bananas following 1, 6, and 10 days of storage. The star graphic patterns were different in the unripe and ripe bananas. In particular, glutamine and asparagine were present as two major components making up 65.68 to 71.75% and 10.86 to 14.94% of the total amino acids. The compositions (%) of valine, leucine, γ-aminobutyric acid, and glutamic acid were significantly increased by 65–210% in ripe bananas following 10 days of storage. In addition, the total composition (%) of essential amino acids was significantly increased at 10 days by comparison with those of 1 and 6 days. Therefore, the present amino acid profiling protocol combined with star pattern analysis has been shown to be useful for the monitoring of the ripening of bananas.